Choosing and using statistics : a biologist's guide - Dytham, Calvin (Hoboken, NJ : Wiley-Blackwell, 2011)
'Choosing and Using Statistics remains an invaluable guide for students using a computer package to analyse data from research projects and practical class work. The text takes a pragmatic approach to statistics with a strong focus on what is actually needed. There are chapters giving useful advice on the basics of statistics and guidance on the presentation of data. The book is built around a key to selecting the correct statistical test and then gives clear guidance on how to carry out the test and interpret the output from four commonly used computer packages: SPSS, Minitab, Excel, and (new to this edition) the free program, R. Only the basics of formal statistics are described and the emphasis is on jargon-free English but any unfamiliar words can be looked up in the extensive glossary. This new 3rd edition of Choosing and Using Statistics is a must for all students who use a computer package to apply statistics in practical and project work. Features new to this edition: * Now features information on using the popular free program, R * Uses a simple key and flow chart to help you choose the right statistical test * Aimed at students using statistics for projects and in practical classes * Includes an extensive glossary and key to symbols to explain any statistical jargon * No previous knowledge of statistics is assumed'--
Keywords: Biometry